Investigations on the prevalence of enzootic bovine leucosis in cattle of Elazig province and its vicinity - Yilmaz, K; Gul, Y; Ozdemir, H; Bolat, Y (Tubitak Scientific & Technological Research Council Turkey, 1997)
Aim of the study was to determine the prevaiance of enzootic bovine leucosis (EEL) in Elazig region. The cattle used in the study were belonged to public animal husbandry units and to Firat University Research and Application Farm. Most of the Cattle in public units were imported to this region from outside the country. The study was performed between September 1993 and September 1994. A total of 1300 blood samples were collected. Once, twice and three times consecutive blood samples were collected from 147, 86 and 327 animals, respectively. In the sampling periods, the cattle were examined clinically. The cattle which were dubious EBI were examined systematically. In hematological examinations; packed cell volumes (PCV %), total white blood cell counts, lymphocyte rates and its counts were determined. In serological examinations; a commercial enzyme immuunoassay (EIA) kit (CHEKIT-Leucotest, serum) was used. In none of the cattle, lymphosarcoma was seen. During hematological examinations; 3.4% of cattle once. 1.2% of cattle twice and 0.8% of cattle three times were dubious for the presence of EBL. However, 0.4% of cattle were positive for EBL during the same examination. None of these animals were BLV (bovine leucose virus)-seropozitif. Serological examinations indicated that 0.08% of serum samples had anti-BLV antibodies only once. These animals did not show any anti-BLV activity during first two sampling period. The percentage of serum samples with seropositivity in two consecutive samples was 0.15. The rate of serum samples with seropositivity in all three sampling periods was 0.5%. All of the seropositive samples were obtained from the University Farm animals. Of the seropositive samples 1.8%, 2.4% and 7.1% were seropositive during the single, two or three examinations. respectively. Animals which were seropositive during the ail three sampling peridos were considered as EEL positive. EEL positivity among ail the cattle investigated in the study was 0.5%. However, the EEL seropositivity in the herd was 7.1%. Only one BLV-seropositive cattle had persistent lymphocytosis. Furthermore, BLV-seropositive cattle had a tendency for anemia and lymhocytosis.
Keywords: cattle; lymphatic; leucosis; prevalence; Elazig